2019
DOI: 10.4236/fmar.2019.72007
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the Portal Vein: Ultrasound Anatomy about 1000 Cases

Abstract: Aim: The aim of this study is to determine from a series of 1000 cases the usual dimensions of the portal vein according to the medical ultrasound. Methodology: We realized a transverse study over 2 years (from January 2015 to December 2017). It concerned an ultrasound exploration of the portal vein. The studied population was healthy voluntary subjects visible without history of abdominal trauma and abdominal operating scar. Results: The average age was 39 years ± 12.16 with extremes of 19 years and 70 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The transverse diameter of the portal vein near its termination varied between 8 and 10 mm in 56.9% cases. 19 Harsimarjith Kaur reported the average length of main portal was found to be 62.9 mm and average breadth of Portal vein at its midpoint between its formation and termination was found to be 16.8 mm. 20 In previous study reported by Arora the length of Right portal vein was 1.3-2.3 cms.…”
Section: Discussionmentioning
confidence: 97%
“…The transverse diameter of the portal vein near its termination varied between 8 and 10 mm in 56.9% cases. 19 Harsimarjith Kaur reported the average length of main portal was found to be 62.9 mm and average breadth of Portal vein at its midpoint between its formation and termination was found to be 16.8 mm. 20 In previous study reported by Arora the length of Right portal vein was 1.3-2.3 cms.…”
Section: Discussionmentioning
confidence: 97%